Reflection loss performance of hexagonal base pyramid microwave absorber using different agricultural waste material - Nornikman, Hassan; Fareq, Malek, Dr.; Soh, Ping Jack; Azremi, Abdullah Al Hadi (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/